Molecular structure and catalytic mechanism of fungal family G acidophilic xylanases - Dey, Protyusha; Roy, Amit (3 Biotech, 2018)
Industrial applications of xylanases have made this enzyme an important subject of applied research work. Function of this particular enzyme is to degrade or hydrolyze the plentiful polysaccharide xylan, an important component of hemicellulose. It mainly cleaves the backbone of xylan that is made up of a number of xylose residues connected with β-1,4-glycosidic linkages. Fungi with mycelia are regarded as the best producer of xylanases. These varied xylanases not only differ in their sizes and shapes but also differ in their physicochemical properties. Depending on the optimum pH in which they work best, they have been classified into (1) acidophilic xylanases active at low pH or acidic pH range, (2) alkaliphilic xylanases that are active at high or alkaline pH range and (3) neutral xylanases having pH optima in the neutral range between pH 5 and 7. Other researchers have classified the xylanases also on the basis of their structural properties, kinetic parameters, etc. This review discusses the molecular structures of some acidophilic xylanases and the molecular basis of low pH optima observed for their activities. It also discusses their unique catalytic mechanism and actual role of the catalytic residues found in them. Apart from these, the review also discusses different applications of these acidophilic xylanases in different industries. The article concludes with brief suggestions about how these acidophilic xylanases can be created employing the techniques of genetic engineering and concepts of synthetic evolution, using the traits of the known acidophilic xylanases discussed in the review.